Analisis Quality of Service Jaringan WLAN Metode PPDIOO Pada Jurusan Kesehatan Gigi Poltekkes Tasikmalaya - Zahra Ramadhani Putri; Elsa Novia Safitri; Helmy Dzulfikar (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2026)
This study aims to evaluate the quality of WLAN network services at the Department of Dental Health, Poltekkes Tasikmalaya, which has a bandwidth of 150 Mbps but frequently experiences connectivity issues. The method used is PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) with Quality of Service (QoS) parameters based on the TIPHON standard. Measurements were conducted at 15 locations using the nPerf and Wireshark applications. Observation results indicate several critical points, such as the Auditorium and the D4 Faculty Room, fall into the "Poor" category with packet loss reaching 89%. As a solution, a proposed topology was designed through Cisco Packet Tracer simulation, which includes the addition of access points and account-based bandwidth management. The simulation results show an improvement in service quality, reaching the "Good" to "Excellent" categories.